The Influence of Hotel Communication Practices on Managers' Communication Satisfaction with Limited English–Speaking Employees. (November 2014) - Dawson, Mary; Madera, Juan M.; Neal, Jack A.; Chen, Jue
Communication satisfaction is an important antecedent to significant work outcomes. Therefore, this study examines how organizational practices influence the communication satisfaction of lodging managers. The results showed a strong correlation between organizational practices that deal with language barriers and the communication satisfaction of the managers. Management awareness and encouragement to improve English skills were independently correlated with communication satisfaction. However, translation of documents and translation by coworkers alone were not correlated with communication satisfaction. This was significant because the results showed that the majority (62.8%) of managers rely on a translator, typically a bilingual employee, to communicate for them. More than half of the respondents (53.5%) reported that top management has paid attention to language barriers in the workplace. In fact, 46.5% stated that their company encourages employees with limited-language skills to improve by offering English at work programs.